Effectivity of wash/malaria educational community-based intervention in reducing anemia among preschool children from Bengo, Angola - Fançony, Claudia (2019)
Exclusive therapeutic approaches promptly clear infections, however, in heavily contaminated environments high reinfections and incidence rates may occur limiting the sustainability of these approaches. Integrating therapeutic and preventive WASH/malaria educational strategies can simultaneously treat infections and reduce disease transmission, resulting in reduced anemia. This study, nested into a major research project investigating the efficacy of educational approaches in reducing anemia, was conducted in 2015 /2016 in CISA's study area, located in Bengo - Angola, and included 312 children randomized to the WASH/Malaria arm. Demographic, socio-economic, Water, Sanitation, Hygiene, and Malaria parental practices, and parasitological and biochemical data were collected at baseline and at 12-month follow-up. These moments were intercalated with 3 monthly domiciliary educational visits aiming at increasing the health literacy of caretakers and collect indicators of changed/improved behavior. T-student, McNemar Test, and Chi-2 tests were used to determine variations on the primary and secondary outcomes. 202 children have completed the study. Despite that, the mean hemoglobin increased levels and total anemia prevalence reduction were not statistically significant (from 11.2g/dL to 11.4g/dL, p=0.21 and from 38.6 to 33.2%, p= 0.21 respectively), an 8.4% reduction in the Iron Deficiency Anemia prevalence was observed (p=0.01). A significant increase in the prevalence of infections was observed, mainly P. falciparum (1.5 to 6.4%), G.lamblia (9.2 to 20.6%), and A. lumbricoides (6.1 to 26.7%). 50.5% of children’s hands and 43.4% of the household’s observations scored 5-6 points for the cleaning state of the nails and for the cleaning state of latrines, respectively. 81.2% of the households scored 0-1 point regarding having water in the latrine to wash hands, 53.3%, 60.1%, and 78.5% were observed to have garbage, loose domestic animals, or puddles in the home surroundings. Neither the reduction of IDA nor the increased infection prevalence were found to be statistically associated with the educational process indicators collected here.